Symptomatic patients remain at substantial risk of arterial disease complications before and after endarterectomy or stenting - Hobeanu, Cristina; Hennerici, Michael G. (Stroke, 2017)
Background and Purpose: After carotid endarterectomy (CEA) or carotid artery stenting (CAS) in patients with transient ischemic attack or minor ischemic stroke, recurrent stroke risk falls to a low rate on modern medical treatment. Methods: We used data from 4583 patients with recent transient ischemic attack or minor stroke enrolled in the TIAregistry.org to perform a nested case-control analysis to evaluate pre- and post-CEA/CAS risk. Cases were defined as patients with a CEA/CAS during the 1-year follow-up period. For each case, 2 controls with a follow-up time greater than the time from qualifying event to CEA/CAS were randomly selected, matched by age and sex. Primary outcome was defined as major vascular events (MVE, including stroke, cardiovascular death, and myocardial infarction). Results: The median delay from symptom onset of qualifying event to CEA/CAS was 11 days (interquartile range, 6-23). Overall, patients with CEA/CAS had a higher 1-year risk of MVE than other patients (14.8% versus 5.8%; adjusted hazard ratio, 2.40; 95% confidence interval, 1.61-3.60; P<0.001). During the matched preprocedural period, MVE occurred in 14 (7.5%) cases and in 13 (3.5%) controls, with an adjusted odds ratio =2.46 (95% confidence interval, 1.07-5.64; P=0.03). In the postprocedural period, the risk of MVE was also higher in cases than in controls (adjusted P<0.03). Conclusions: Patients with CEA/CAS had a higher 12-month risk of MVE, as well as during pre- and postprocedural periods. These results suggest that patients in whom CEA/CAS is anticipated are likely to be an informative population for inclusion in studies testing new antithrombotic strategies started soon after symptom onset.